Medale Jana III Sobieskiego pochodzące z okresu pomiędzy elekcją a koronacją (1674-1676) - Rokita, Jan Gustaw (Studia Europaea Gnesnensia, 2019)
The chief aim of this paper is to acquaint the reader with three medallic pieces showing Jan III Sobieski, whilst trying to answer what kind of propa-ganda they may have served. The author provides an iconographic analysis and comparisons with other depictions in medals, graphic arts, sculpture, and handicraft.